TWEAK/Fn14 axis may promote vascular smooth muscle cell senescence via p38 signaling pathway: preliminary evidence - Chunyang Wei; Xiaoying Liu; Zhuang Miao; Hua Zhang; Yanfu Wang; Guoxian Qi (Future Science OA)
Aim The primary objective of this study is to investigate the impact of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its functional receptor, fibroblast growth factor-inducible 14 (Fn14), on the process of vascular smooth muscle cell (VSMC) senescence.Methods Rat arterial VSMCs were cultured with angiotensin II to establish a model of premature senescence. The effects of TWEAK and Fn14 on senescent VSMCs were evaluated. Additionally, the role of p38 phosphorylation pathway in the effect of TWEAK on VSMCs senescence was assessed.Results Expressions of TWEAK and Fn14 were significantly elevated in senescent VSMCs. TWEAK activated the p38 phosphorylation pathway and promoted the SA-β-gal staining and P53 expression.Conclusion These preliminary findings suggest that the TWEAK/Fn14 axis may play a crucial role in promoting VSMC senescence.